Information and measuring system on the basis of strain sensors based on silicon microcrystals - Druzhinin, A. O.; Kutrakov, O. P.; Nichkalo, S. I.; Stasiv, V. M. (Technology and design in electronic equipment, 2018)
One of the promising directions of development of information and measuring systems for monitoring and diagnostics is the use of intelligent sensors of various physical quantities, in particular pressure, temperature, deformation, acceleration, etc. The main functional feature that distinguishes such sensors is the possibility of signal processing directly in the measuring zone, which involves the temperature compensation of the output signal, linearization of the transformation function. Along with primary converters, intelligent sensors include analog-to-digital and digital-to-analog converters, microcontroller, memory-storage device, input/output interfaces. However, the technologies used today for the creation of existing microelectronic sensors are quite complex and require special process equipment and materials, that leads to an increase in their value.The aim of this work is to develop an information and measurement system for use in conjunction with mechanical sensors based on strain gauges made of silicon whiskers in terms to provide a higher efficiency.The deformation and temperature characteristics of sensors of mechanical quantities (pressure, force and deformation) with strain gauges on the basis of p-type Si whiskers (ρ=0.005-0.02 Ω·cm) in the temperature range from -60 to +60°C were analyzed. It has been established that at a deformation level of +–6·10–4 relative units, the high values of sensitivity and linearity of strain gauge characteristics are maintained, and the hysteresis effect due to the characteristics of elastic elements is shown to the smallest extent. It is shown that the temperature dependence of relative change in the resistance of strain gauge resistors based on p-Si whiskers with resistivity of 0.005 Ω·cm is characterized by the smallest nonlinearity. This simplifies the problem of compensation of the temperature errors, which are typical for such sensors. The temperature coefficient of resistance for strain gauges was found to be 0.15%/°N.The information and measuring system was developed on the basis of pressure sensor with strain gauges made of silicon whiskers (ρ=0.005 Ω·cm). This pressure sensor provides the simultaneous measurement of pressure and temperature in the ranges 0...100 kPa and –60...+60°N, respectively. The measuring channel of the developed system was based on the AVR ATmega328P microcontroller, which provides the ability to create modern high-precision distributed data gathering and display systems. As a result of testing, satisfactory results were obtained regarding stability, sensitivity and measurement ranges of the developed information and measuring system. The main measurement error did not exceed 0.1%.The measuring circuit can be easily adapted to a new task without making any significant changes to its hardware, the function of the device is easily adjusted by changing the work program.